Karakteristik Elemen Arsitektur Terapeutik di Ruang Terapi Rehabilitasi Narkoba LIDO Bogor - O'i Prasesti; Syam Rachma Marcillia (Universitas Muhammadiyah Palembang, 2025)
The implementation of therapeutic architectural elements within therapy rooms must be conducted appropriately, necessitating thorough evaluation to ensure alignment with established design standards and recommended criteria. The key architectural elements observed in this study include openings, color schemes, natural lighting, and material selection. The objective of this research is to examine the characteristics of therapeutic architectural elements at the National Narcotics Board (BNN) Lido, recognized as one of the largest rehabilitation centers in Indonesia. This study employs a descriptive qualitative approach, with data collected through direct observation in rehabilitation therapy spaces. The aim is to describe the existing conditions of therapeutic architectural elements applied in both counseling rooms and group therapy rooms. Findings indicate that, in general, the therapeutic architectural elements in counseling rooms do not fully comply with several recommended design standards. For instance, the dimensions of window openings, indoor temperature, and levels of natural light illumination fall short of the prescribed benchmarks. Conversely, the therapeutic architectural elements in group therapy rooms largely conform to the recommended design standards and criteria.